The Impact of Audio-Visual Aids on Learning English among MSU Third-Year Students - Al Aqad, Mohammed H.; Al-Saggaf, Mohammad A.; Muthmainnah, Muthmainnah (Institut Agama Islam Negeri (IAIN) Curup, 2021)
This study investigates the efficacy of audio-visual technologies in assisting MSU third-year students in learning English vocabulary. The interplay of audio-visual aids in educational conversations has been researched from a variety of perspectives (Tuovinen, 2000). Multimedia is a multimodal experience in which information is communicated through text, graphics, pictures, audio, and video. It has been demonstrated that a combination of words and images always carries a substantial quantity of information (Mayer, 2018: 55). The use of multimedia in teaching and learning. The goal of this research is to determine the efficiency of audiovisual aids in the learning of English vocabulary among MSU third-year students. The use of multimedia in instruction and learning threatens the foundations of higher education. The current study investigates how third-year students at Malaysia's Management and Science University use multimedia in their English studies (MSU). To fulfill the study's aims, the researchers used both a qualitative and quantitative approach. An online poll of 200 students enrolled in the Bachelor of English as a second language program was used to construct the study corpus (BTESL). In addition, 150 MSU students from the same program were polled. The study's findings indicate that multimedia inspires BTESL students to learn English creatively and engagingly. It also aroused students' attention and compelled them to learn new terms. Multimedia, according to the study, is an excellent tool for third-year English students. It also helps students enhance their understanding of correct terminology and language.